Diabetic nephropathy and inflammation - Duran-Salgado, Montserrat B (Baishideng Publishing Group Inc, 2014)
Diabetic nephropathy (DN) is the leading cause of end-stage renal failure worldwide. Besides, diabetic nephropathy is associated with cardiovascular disease, and increases mortality of diabetic patients. Several factors are involved in the pathophysiology of DN, including metabolic and hemodynamic alterations, oxidative stress, and activation of the renin-angiotensin system. In recent years, new pathways involved in the development and progression of diabetic kidney disease have been elucidated; accumulated data have emphasized the critical role of inflammation in the pathogenesis of diabetic nephropathy. Expression of cell adhesion molecules, growth factors, chemokines and pro-inflammatory cytokines are increased in the renal tissues of diabetic patients, and serum and urinary levels of cytokines and cell adhesion molecules, correlated with albuminuria. In this paper we review the role of inflammation in the development of diabetic nephropathy, discussing some of the major inflammatory cytokines involved in the pathogenesis of diabetic nephropathy, including the role of adipokines, and take part in other mediators of inflammation, as adhesion molecules.